Analysis Public Sector Leadership and Influencing Factors Service Licensing in Government Regency Bojonegoro - Setyo Hartono; Soesilo Zauhar; Bambang Santoso Haryono; Tjahjanulin Domai; Abd. Qadir Muslim (Al-Makki Publisher, 2025)
Research This aim For analyze Public Sector Leadership in service licensing in the government Regency Bojonegoro and for analyze supporting and inhibiting factors in Public Sector Leadership in service licensing in the government Regency Bojonegoro. Research This approach qualitative method studies case. Data collection techniques using observation, interviews, documentation, and Focus Group Discussion (FGD). Data analysis was carried out with a number of stages, which is open coding, axial coding, and selective coding. The process of analyzing and extracting data conclusions researchers also use technique triangulation, namely triangulation method, between researchers, data sources and theories. The results of study This show draft Public Sector Leadership can increase service public field licensing optimally in the Regency Bojonegoro. Public Sector Leadership carried out by the Head of the Bojonegoro Regency Bojonegoro realized with existence commitment leader, style leadership and culture unified organization with room scope performance as well as existence plan proper work. Factors influential supporters Public Sector Leadership in service licensing in the Regency Bojonegoro is : commitment tall Regional Head, culture appropriate organization with room scope performance government, the existence of motivation and innovation from Regional Heads and transparency. Meanwhile, the factor inhibitor among others: sources Power apparatus that has not Can follow initiative leaders and dependencies public to leaders, lack of appreciation leader to performance employee, not yet complete regulations field licensing and society Still Not yet used to with technology.